Effects of growth regulators on in vitro embryogenesis of nucelli in Citrus sinensis cv. Valência - Pasqual, Moacir; Ando, Akihiko; Crócomo, Otto Jesu (Pesquisa Agropecuaria Brasileira, 2014)
This paper describes the attempts to determine the methodology for regeneration of plants from nucelli. Nucelli were extracted from 'Valência' fruits (C. sinensis Osb.) twelve weeks after pollination and cultivated in vitro on "MS" mineral salts supplemented with (mg/l): thiamine HCL, 0.2; pyridoxine HCL, 1.0; nicotinic acid, 1.0; mesoinositol, 100; malt extract, 500; sucrose, 50.000; agar, 8.000; pH, 5.7. The treatments were combinations of kinetin (0.0; 0.25; 0.50; 1.0 and 1.5 mg/l) and 2,4 - diclorofenoxyacetic acid (D) (0.0; 0.5; 1.0 and 2.0 mg/l) with ten replications in dark and ten in light (1.500 lux) at 27oC ± 2oC. It was possible to get twelve nucellar embryos from a single nucellus. Kinetin and 2,4-D inhibited the embryogenesis. Ocasionally the formation of globular callus with high embryogenic potential was observed mainly in 0,25 mg/l kinetin and 0,5 mg/l 2,4-D medium.